Women and Cultural Patriarchy in Politics - Wayan, Krisna Yuda I; Nyoman, Subanda (Budapest International Research and Critics University, 2020)
This study aims to determine the political phenomena of women in a patriarchal culture in Gianyar Regency, Bali and to find out the perception of the community in Gianyar Regency, Bali on women's representation in the 2019 legislative elections. This study uses a descriptive qualitative approach. The sampling technique in determining informants used the purposive sampling method. Data collection is done through observation. Interview and documentation study. The results showed that the phenomenon of patriarchal culture influenced the political participation of women in Gianyar Regency, Bali. The low representation of women legislative members is due to the patriarchal culture which is still thick in Bali, especially the people in Gianyar Regency. Patriarchal culture is a major obstacle that hinders the political participation of Balinese women. Also, there are besides several other factors such as education and public understanding of the use of political rights for each community, the limitations of information media, human resources, and financial resources, cause the low participation of women in politics.